Parental influences on children’s Body Mass Index (BMI) level among kindergarten pupils in Tadika Tengku Anis II, Kota Bharu, Kelantan / Noramirah Che Omar, Ummi Nabihah Mohd Azhar and Nur Farhan Natasha Mohamad Nasir - Che Omar, Noramirah; Mohd Azhar, Ummi Nabihah; Mohamad Nasir, Nur Farhan Natasha (2017)
Being underweight has a marked effect on one’s physical health specifically on heart and circulation system, sex hormones and fertility, bones’ strength and others. In Peninsular Malaysia, studied done by Khor and Tee (1997) stated that 32.6% of the boys and 35.9% of the girls were underweight among children aged 1 to 6 years old. In this case, family lifestyles can contribute on the eating behaviour of their children and finally the outcome of their weight. Thus, this study was conducted to investigates the parental influences factors that affecting the children's Body Mass Index (BMI) level among kindergarten pupils aged 5 to 6 years old in Tadika Tengku Anis II, Kota Bharu, Kelantan. The cross sectional design was used for this study and the sample size of 148 pupils from all the pupils in Tadika Tengku Anis II, Kota Bharu, Kelantan was obtained using Proportionate Stratified Random Sampling technique. A validated self-administered questionnaire was used as a data collection tool for this study. This study also uses Descriptive Statistics, Chi-square Test of Independence, Independent T-test and Binary Logistic Regression analysis to examine these factors that affecting the children's Body Mass Index (BMI) level. The prevalence of underweight amongst kindergarten pupils was 58.10%. The results have showed that there was no significant association on the children's Body Mass Index (BMI) level based on gender. Besides, there was also no significant mean difference in the children's Body Mass Index (BMI) level between the parental influences factors. The finding also indicated the factors that affecting the children's Body Mass Index (BMI) level were only Parental Nutritional Knowledge and gender for boys. In order for this study to obtain more precise results, it was recommended to apply other sampling techniques such as cluster sampling and also to use face-to-face interview as the data collection method